(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the history of the creation of polymers, their structure, types and stages of production. The terms monomer and polymer and their meaning are explained. The regulatory and legal analysis of the legislative base of the Republic of Uzbekistan on polymer materials has been carried out. The content and essence of the international Basel and Stockholm Conventions, as well as the scope of application, are shown. The grounds of the relevant regulatory documents for the benefits and restrictions provided for the import and export of polymers in foreign economic activity are shown. Such processes as identification of types of polymer products in foreign economic activity, exemption from customs duties, provision of guarantees and compensations, restrictions on polyethylene terephthalate (PET) waste, fragments and waste, application of excise tax on polyethylene granules and handling of polymer waste are highlighted.